IMPLEMENTASI METODE PROTOTYPING DALAM PENGEMBANGAN SISTEM INFORMASI AKADEMIK SMA TUNAS KARYA - Elis Sondang Dasawaty (Institut Bisnis dan Informatika Kwik Kian Gie, 2015)
Nowadays, a lot of schools already used computer-based information systems. By using computer-based information system, it certainly facilitate the process in schools. Tunas Karya senior high school is one of the schools that want to use computer-based information systems. Tunas Karya senior high school had established for 24 years and along with the development of information systems, Tunas Karya senior high school wants to use computer technology to further reduce the error rate in recording data and simplify the data search. The purpose of this research is to design information systems that use computer technology to Tunas Karya senior high school. In the system being designed for SMA Tunas Karya, there are a variety of features that will be used by SMA Tunas Karya for ease in recording and data search. Designed system also has the ability to generate a schedule, assessment, presence, and printing reports that can be used for ease in viewing the desired data Advice can be given is for the future of this system can be developed by creating a web site so that students can still view the value of their data when they are not in school and teachers can enter the data value when not in school. Keywords: school, academic information systems, prototyping.